2018
DOI: 10.1002/pssa.201700945
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Cu2ZnSn(SxSe1‐x)4 by First‐Principles Calculations

Abstract: Structural, electronic, and optical properties of Cu 2 ZnSn(S x Se 1-x ) 4 semiconductors are studied theoretically for different concentration of S and Se anions. The optical properties are calculated at three levels of theory, in the generalized gradient approximation (GGA), meta-GGA, and with a hybrid functional. The GGA and meta-GGA calculations are corrected with an onsite Coulomb U d term. Lattice constants, dielectric constants, and band-gaps are found to vary almost linearly with the concentration of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…< E1B for Ge04 sample and E1A >E1B for Ge08. Nevertheless, this result is consistent with the order of high-energy transitions in Cu2ZnGeSe4 and Cu2ZnSiSe4 [48] and is most likely related to the crystal structure transformation from kesterite to the wurtz-stannite type for x<0.37 in Cu2Zn(GexSi1-x)Se4 solid solution [31]. It is also should be added that the highest energy transitions (4.18 eV for Ge08 sample and 5.32 eV for Ge04) are determined with less accuracy because they occur near or beyond the experimental spectral range.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…< E1B for Ge04 sample and E1A >E1B for Ge08. Nevertheless, this result is consistent with the order of high-energy transitions in Cu2ZnGeSe4 and Cu2ZnSiSe4 [48] and is most likely related to the crystal structure transformation from kesterite to the wurtz-stannite type for x<0.37 in Cu2Zn(GexSi1-x)Se4 solid solution [31]. It is also should be added that the highest energy transitions (4.18 eV for Ge08 sample and 5.32 eV for Ge04) are determined with less accuracy because they occur near or beyond the experimental spectral range.…”
Section: Resultssupporting
confidence: 85%
“…Based on our results and those reported for Cu2ZnGeSe4 (x=1.0, E0~1.4 eV) and Cu2ZnSiSe4 (x=0, E0~2.3-2.4 eV) [18,25], it reveals that band gap varies nonlinearly with composition for the Cu 2 Zn(Ge x Si 1-x )Se 4 alloys. It has been recently calculated that the bowing parameter, that describes nonlinear dependency of the band gap dependence, is 0.56 for the kesterite Cu2Zn(GexSi1-x)Se4 solid solution [48]. This relatively high value of bowing coefficient could explain the observed band gap dependency.…”
Section: Resultsmentioning
confidence: 96%
“…In recent years, researchers have aimed to reveal the defect formation mechanism and passivation strategies. For example, extensive theoretical and experimental studies by the group of Persson [83][84][85] and Carter [86][87][88] have shown that Na, Ca, Cd, Si, and Ge as alloying elements are expected to enhance the performance of CZTSSe devices. In 2017, Qi et al dissolved silver elements in 1,2-ethylene glycol and 1,2-ethylenediamine solvents and obtained CAZTSSe (Ag/(Cu + Ag) = 3%) solar cells up to 10.36%, and they observed that the grain growth of the absorbers is significantly improved, which is beneficial to the improvement of the I-V characteristics of CZTSSe.…”
Section: Pv Applications For Amine Thiol-based Routesmentioning
confidence: 99%
“…[12] from absorption spectra measurements. Figure 4 shows the trend in Eg, which can be fitted to a parabolic form Eg(x) = (1x) Eg(0) + xEg(1)b•x(1x), where b is the bowing parameter [15]. It should be pointed out that all experimental points presented in the Fig.…”
Section: Fig 4 Band-gap Energies Of Cu2znsn(sxse1-x)4 Solid Solutions...mentioning
confidence: 99%
“…Therefore, the next step in order to increase the efficiency of the solar absorbers based on CZTSSe semiconductors should be the fundamental study of their intrinsic properties with the aim to understand and to minimize all the detrimental effects. At the moment there are only few studies referring to the Raman [2,6,8-10], structural [2,7,11] and optical properties [3,5,[12][13][14][15][16], including a comprehensive study on the optical properties of kesterite Cu2ZnSn(SxSe1-x)4 with intermediate sulfur content (0.2<x<0.4) [13]. This last study was conducted by combining both experimental (spectroscopic ellipsometry (SE) on CZTSSe thin film absorbers) and theoretical (ab initio calculations) methods that led to the determination of the dielectric functions, bandgaps Eg and critical points (CP) transition energies E0 and E1 [13].…”
Section: Introductionmentioning
confidence: 99%